Auditory neglect in patients with Alzheimer's disease - Herrero Romero, Marta; Thuissard, Israel J.; Sanz-Rosa, David; Ruiz Escudero, Carlos; Vidal López, Joaquin; Domínguez Ovejas, Silvia Verónica (Auditio, 2021)
Introduction. Hearing neglect is a dysfunction of the central nervous system that causes difficulties in responding to a stimulus on the opposite side of the injury, when sounds or words are presented by both ears at the same time. The main objective of this work is to assess the existence of auditory neglect in patients with grade I Alzheimer's disease. Material and methods. In this work, 32 individuals have been analyzed, divided into two groups. 16 patients diagnosed with grade I Alzheimer's disease and 16 control individuals (without Alzheimer's disease or other neurological pathologies). The ages of the subjects were between 60 and 95 years. For the assessment of auditory neglect, the Auditory test and the Dichotic Digits Test were applied. Results. The Auditory test detected that when two simultaneous stimuli were presented by both ears, patients with Alzheimer's disease grade I perceived 72.5% of the tones through the left ear, likewise, the results of the Dichotic Digits Test showed a lower number of hits in the right ear of these patients. The results of both the Auditory tests and the Dichotic Digits Test performed on the control group did not show statistically significant differences between the two ears. Conclusion. The results obtained suggest that patients with grade I Alzheimer's disease have left auditory neglect.